Prenatal diagnosis and molecular genetic analysis of recurrent trisomy 18 of maternal origin in two consecutive pregnancies - Chih-Ping Chen; Fang-Tzu Wu; Chian-Huey Wong; Shin-Wen Chen; Schu-Rern Chern; Yen-Ting Pan; Wen-Lin Chen; Wayseen Wang (Elsevier, 2023)
Objective: We present prenatal diagnosis and molecular genetic analysis of recurrent trisomy 18 of maternal origin in two consecutive pregnancies. Case report: A 37-year-old, gravida 3, para 1, woman was referred for genetic counseling because of cystic hygroma on ultrasound at 12 weeks of gestation, a previous pregnancy with a fetus with trisomy 18, and an abnormal first-trimester non-invasive prenatal testing (NIPT) result of Z score of 9.74 (normal: −3.0-3.0) in chromosome 18 suggesting trisomy 18 during this pregnancy. The fetus died at 14 weeks of gestation, and a malformed fetus was terminated at 15 weeks of gestation. Cytogenetic analysis of the placenta revealed a karyotype of 47,XY,+18. Quantitative fluorescent polymerase chain reaction (QF-PCR) assays on the DNA extracted from parental bloods and umbilical cord determined a maternal origin of trisomy 18. One year previously, the woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age of 36 years. Amniocentesis revealed a karyotype of 47,XX,+18. Prenatal ultrasound was unremarkable. The mother had a karyotype of 46,XX, and the father had a karyotype of 46,XY. QF-PCR assays on the DNA extracted from parental bloods and cultured amniocytes determined a maternal origin of trisomy 18. The pregnancy was subsequently terminated. Conclusion: NIPT is useful for rapid prenatal diagnosis of recurrent trisomy 18 under such a circumstance.